2009
DOI: 10.1002/ajim.20774
|View full text |Cite
|
Sign up to set email alerts
|

Costs by industry and diagnosis among musculoskeletal claims in a state workers compensation system: 1999–2004

Abstract: This study provides insight into the severity (i.e., medical and indemnity costs) of MSDs across multiple industries, providing data for prioritizing of resources for research and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 26 publications
1
79
1
Order By: Relevance
“…Mroz et al 2014 reported an average total cost (medical plus indemnity) of $6,785 for 232,399 WC claims in Maryland. Dunning et al reported an even lower average cost of $5,130 for 572,508 WC claims in Ohio (Depue, Kagey, & Heid, 1985;Dunning et al, 2010;Ferguson, Marras, Allread, Knapik, & Splittstoesser, 2012;Leigh et al, 2001;Leigh et al, 2003;Mroz et al, 2014;Siwek, 2007). Both of these compensation rates pale in comparison to the average cost per claim for CA industries in general ($38,900) and the CA FMP industry ($38,400).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mroz et al 2014 reported an average total cost (medical plus indemnity) of $6,785 for 232,399 WC claims in Maryland. Dunning et al reported an even lower average cost of $5,130 for 572,508 WC claims in Ohio (Depue, Kagey, & Heid, 1985;Dunning et al, 2010;Ferguson, Marras, Allread, Knapik, & Splittstoesser, 2012;Leigh et al, 2001;Leigh et al, 2003;Mroz et al, 2014;Siwek, 2007). Both of these compensation rates pale in comparison to the average cost per claim for CA industries in general ($38,900) and the CA FMP industry ($38,400).…”
Section: Discussionmentioning
confidence: 99%
“…This fatality rate per injury is more than three times greater than found in manufacturing and construction, which are seemingly more dangerous fields (Klowden, Chatterjee, & Hynek, 2010;Leigh, McCurdy, & Schenker, 2001;Rossol, 2011;Rules) tissue) represent the vast majority of WC claims in the FMP industry, they also may represent a significant impact on orthopaedic and other musculoskeletal practices, particularly in areas associated with the FMP industry such as Hollywood in California or Mumbai, India (the base of Bollywood). Some studies have analyzed the cost of WC claims in industry at large (Dunning et al, 2010;Hoe, Urquhart, Kelsall, & Sim, 2012;Leigh et al, 2001;Leigh, Yasmeen, & Miller, 2003). However, there is presently no comprehensive data on the cost of WC claims in the FMP industry, let alone in regard to musculoskeletal injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar spine (34.1%), shoulder (30.6%), and neck spine (30.3%) were parts of the body that received the highest percentages in this field. Moreover, the highest cost for compensation claim was $8,750 for lumbar spine, $7,562 for neck spine, and $6668 for shoulder, respectively (5). The cost of cervical and upper limb disorders in the Nordic countries was estimated at around 2% to 5% of gross national product, and in the UK, the costs of upper limb disorders associated with work was estimated at around 1.25 billion pounds annually (6,7) In 1995, about 4.2 million working days were lost due to musculoskeletal disorders in the upper limbs and neck (8).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, in the United states, 29% of the injuries and illnesses requires a median of 10 days for sick leave due to the impact of work-related musculoskeletal disorder (WMSD) [4]. Additionally, the compensation costs, lost wages, and lost productivity caused by WMSD, is annually between $45 and $54 billion [5]. Regarding to this actual cost, the WMSDs impact is absolutely enormous especially if corporate economics is considered.…”
Section: Introductionmentioning
confidence: 99%